Error Analysis of Japanese Language for Tourism: A Study on Tour Guiding in Student Script - Savana Azizia Freda; Lantang Ayu Gardenia (SHS Web of Conferences)
Learning a foreign language for learners in Indonesia is problematic because it is a second or even third language. The cause of foreign language difficulties is an influence of the mother tongue, which is not used in everyday conversation. Japanese learners sometimes make grammatical mistakes when guiding Japanese-speaking tours. This study aims to find out Japanese language errors in guiding tours and the causes of Japanese language errors in guiding tours. In addition, This research is needed for reference for students who learn Japanese as an insight when guiding tours in Japanese. The method used in this study is a descriptive method with a qualitative approach to describe Japanese language errors based on the type and cause of these errors in guiding tours. The data was sourced from a tour guide script in Japanese, including 22 scripts, and the data was 48. The result of this study was there were 13 language error data subtraction (omission/脱落), 20 language error data Addition (付加), 10 language error data misformation (誤formation), and five language error data (位置). Meanwhile, the error in the form of reserve use was not found in the Japanese tour guide script data. The cause of errors that students have made is due to the performance factor, which is not aware that the sentences are incomplete, and the competency factor, which is not understanding the teacher’s explanation in the grammar course.